Why Dental Anthropology Should be Taught in Dental Schools?: Ten Years Experience at the University of Costa Rica - Valerio Alfaro, Irene (2025)
Dentistry and anthropology are now more interconnected than ever, as teeth serve as critical evidence for studying ancient civilizations. Several topics in Dental Anthropology can be effectively integrated into dental school curricula. Currently, the absence of such training in undergraduate and postgraduate programs limits students’ understanding of teeth from a broader, interdisciplinary per-spective, thereby hindering the application of these insights in clinical practice. This article aims to provide an overview of what has been taught during the first ten years of introducing the basic concepts of Dental Anthropology at the Dental School of the University of Costa Rica. Similar projects implemented in Latin America are also discussed. Finally, it examines the achievements, challenges, and strategies to be implemented in the future.